Banking Crises in Transition Economies : Fiscal Costs and Related Issues - Tang, Helena; Zoli, Edda; Klytchnikova, Irina (World Bank, Washington, DC, 2014)
The authors look at strategies for dealing with banking crises in 12 transition economies -- five from Central and Eastern Europe (CEE): Bulgaria, the Czech Republic, Hungary, Macedonia, and Poland; the three Baltic states: Estonia, Latvia, and Lithuania; and four countries from the Commonwealth of Independent States (CIS): Georgia, Kazakhstan, the Kyrgyz Republic, and Ukraine. Three types of strategies were used to deal with the crises. The CEE countries generally pursued extensive restructuring and recapitalizing of banks; most CIS countries pursued large-scale liquidation; and the Baltic states generally pursued a combination of liquidation and restructuring. The strategy pursued reflected macroeconomic conditions and the level of development in a country's banking sector. There were more new banks in the former Soviet Union (FSU-the CIS and Baltic states), but they tended to be small, undercapitalized, and not deeply engaged in financial intermediation. The CEE countries generally incurred higher fiscal costs than the FSU countries but ended up with sounder, more efficient banking systems, with many of the recapitalized banks being privatized to strategic foreign investors. The CIS countries pursued a less fiscally costly approach but have been left with weak banking systems and low levels of intermediation. The Baltic states appear to have struck a good balance, incurring modest fiscal costs while making their systems sounder and more efficient. The findings suggest the following: a) Operational, financial, and institutional restructuring should be undertaken in parallel. b) Financial restructuring should involve adequate recapitalization to deter moral hazard and repeated recapitalization. c) Operational restructuring should entail privatization to core investors (particularly to reputable foreign banks). d) The enterprise problems underlying banking problems must also be addressed. e) Fiscal costs were reduced when governments dealt only with bad debt inherited from the socialist period; when small banks that held few deposits were allowed to fail, where the social costs of such failure were low; and when only banks that got into trouble because of external shocks were rescued while those suffering from poor management were liquidated. f) The government, not the central bank, should undertake bank restructuring. Central bank refinancing is not transparent and could lead to hyperinflation.